Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

Risk of failure of insecticides and Cry/Vip Bt maize hybrids to control field populations of fall armyworm in Brazil - Josélia C.O. França; Hugo M. Monteiro; Rafael M. Pitta; Simone M. Mendes; João G.T. Moraes; Arleide F. Neto; Royner J. Ortiz-Rojas; Rodrigo J.S. Satolo; Leidiana M. Ribeiro; Yann J.M. Campos; Thadeu C. Souza; Eliseu J.G. Pereira (Crop Protection, 2026)

Effect of the genotype and environment interaction on body weight traits in Nelore cattle (Bos indicus) - Raimundo Nonato Colares Camargo-Júnior; Cláudio Vieira de Araújo; Caio de Souza Teixeira; Simone Inoe de Araújo; Raysildo Barbosa Lôbo; Lílian Roberta Matimoto Nakabashi; Letícia M. Mendes de Castro; Flávio Luiz Menezes; André Guimarães Maciel e Silva; José Ribamar Felipe Marques; Welligton Conceição da Silva; Marco Aurélio Lopes Della Flora; et al. (Tropical Animal Health and Production, 2025)

The role of microbial communities in biogeochemical cycles and greenhouse gas emissions within tropical soda lakes - Thierry A. Pellegrinetti; Simone R. Cotta; Yara B. Feitosa; Paul L.A. Melo; Wanderlei Bieluczyk; Antonio M.M. Silva; Lucas W. Mendes; Hugo Sarmento; Plinio B. Camargo; Siu M. Tsai; Marli F. Fiore (Science of The Total Environment, 2024)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.